Effect of Pre-heating on Microtensile Bond Strength of Composite Resin to Dentin. - Abdolrahim Davari; Alireza Daneshkazemi; Behnaz Behniafar; Mahsan Sheshmani (Tehran University of Medical Sciences, 2014)
Direct composite resin restorations are widely used and the impact of different storage temperatures on composites is not well understood. The purpose of this study was to evaluate the microtensile bond strength of composite to dentin after different pre-curing temperatures.Occlusal surfaces of 44 human molars were ground with diamond burs under water coolant and polished with 600 grit silicon carbide papers to obtain flat dentin surfaces. The dentin was etched with 37% phosphoric acid and bonded with Adper Single Bond 2 according to the manufacturer's instructions. The specimens were randomly divided into two groups (n=22) according to the composite resin applied: FiltekP60 and Filtek Z250. Each group included three subgroups of composite resin pre-curing temperatures (4°C, 23°C and 37°C). Composite resins were applied to the dentin surfaces in a plastic mold (8mm in diameter and 4mm in length) incrementally and cured. Twenty-two composite-to-dentin hour-glass sticks with one mm(2) cross-sectional area per group were prepared. Microtensile bond strength measurements were made using a universal testing machine at a crosshead speed of one mm/min. For statistical analysis, t-test, one-way and two-way ANOVA were used. The level of significance was set at P